Removal of Selected Metals from Wastewater Using a Constructed Wetland - Šíma, Jan; Svoboda, Lubomír; Pomijová, Zuzana (Chemistry & biodiversity, 2016)
Removal of selected metals from municipal wastewater using a constructed wetland with a horizontal subsurface flow was studied. The objective of the work was to determine the efficiency of Cu, Zn, Ni, Co, Sr, Li, and Rb removal, and to describe the main removal mechanisms. The highest removal efficiencies were attained for zinc and copper (89.8 and 81.5%, respectively). It is apparently due to the precipitation of insoluble sulfides (ZnS, CuS) in the vegetation bed where the sulfate reduction takes place. Significantly lower removal efficiencies (43.9, 27.7, and 21.5%) were observed for Li, Sr, and Rb, respectively. Rather, low removal efficiencies were also attained for Ni and Co (39.8 and 20.9%). However, the concentrations of these metals in treated water were significantly lower compared to Cu and Zn (e.g., 2.8 ± 0.5 and 1.7 ± 0.3 μg/l for Ni at the inflow and outflow from the wetland compared to 27.6 ± 12.0 and 5.1 ± 4.7 μg/l obtained for Cu, respectively). The main perspective of the constructed wetland is the removal of toxic heavy metals forming insoluble compounds depositing in the wetland bed. Metal uptake occurs preferentially in wetland sediments and is closely associated with the chemism of sulfur and iron.
Keywords: Trace element analysis; Constructed wetland; Lithium; lithium; Strontium; Copper; Municipal sewage; kobalt; Metal pollutants; Zinc; Cobalt; stroncium; zinek; Wastewater; mokřady; měď; nikl; Waste Water; Nickel; Water Pollutants, Chemical; Wastewater treatment; rubidium; odpadní voda; Wetlands; chemické látky znečišťující vodu; Rubidium